PUBLIC HEALTH SERVICES AT FORT RILEY, KANSAS, AND THE ASSESSMENT OF TOBACCO USE AMONG ACTIVE-DUTY PERSONNEL - Ornelas, Samuel (My University, 2010)
In support for the master’s degree in public health, I conducted a field experience at Fort Riley Medical Activity, Department of Public Health, Irwin Army Community Hospital, Fort Riley, Kansas. The objectives for this project were to observe preventive medicine at a patient care level, investigate and manage a communicable and/or reportable disease and conduct a tobacco use prevalence study among active-duty personnel serving on Fort Riley Army post. I was able to gain valuable experience by working under the supervision of Lieutenant Colonel Paul D. Benne MD, MPH, Chief of Preventive Medicine. Chapter one characterizes the Fort Riley community and health services, specifically the department of public health. Chapter two reviews the field experience focusing on patient care observation and disease outbreak investigation. Chapter three presents the tobacco use prevalence study and chapter four displays presentation slides and a poster generated for conference presentation.
Keywords: Fort Riley; Smoking; US Army; Tobacco Use; Public Health; Active-duty; Health Sciences, Education (0350)